Analisis Pengaruh Fasilitas E-Banking, Kualitas Layanan dan Media Sosial Pada Kepuasan Nasabah Serta Loyalitas Nasabah: Studi Kasus Pembukaan Rekening Britama Secara Online di Jabodetabek - Muhamad Akbar Ginanjar; Lamhot Henry Pasaribu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of digital technology has impacted the banking sector, particularly in providing services that increasingly facilitate customers. One example is the BRImo mobile banking app developed by BRI, which integrates mobile banking, internet banking, and electronic money services. This app offers various features, including online account opening, making it easier for customers to conduct banking transactions anytime and anywhere. BRImo has recorded the highest number of users in Indonesia, surpassing other banking apps like BCA and Mandiri. Online account opening through BRImo has proven successful, especially during the COVID-19 pandemic, with the addition of 1.1 million new accounts. This research also discusses a comparison of the online account opening features between BRImo and other banking apps, as well as the role of social media in enhancing customer loyalty. Social media serves as an effective promotional tool and is an important factor in building a positive image and influencing customer satisfaction. Based on previous studies, the quality of e-banking services and social media promotion has been shown to affect customer loyalty. The aim of this study is to analyze the impact of e-banking services, service quality, and social media on customer satisfaction and loyalty at BRI. The findings of this study are expected to provide insights for the development of digital services and marketing strategies for BRI.